Women's Empowerment and the Well-being of Children in Nepal. Issue 2 (June 2020) - Panday, Priniti
This article examines the relationship between women's empowerment and child well-being in Nepal. Various indicators of women's empowerment and child well-being are presented and compared across the seven provinces in the country. A strong positive relationship between the two is established. In fact, women's empowerment appears to have a stronger relationship to children's well-being than wealth indicators.